The Dialectic Relationship between Poetry Metrics and Meaning - boufasse, abd elhamid (Milev Journal of Research and Studies, 2015)
The present study investigates the relationship between poetry metrics and meaning by raising some issues of which metrics scholars and critics of Rhetoric were aware, but held diverging views about them. Not only so, even modern literary criticism has a vague and ambiguous conceptualization over this issue. Added to that, there is some disagreement between those who advocate the existence of an inherit relationship between metrics and meaning and others who deny it altogether. Building on this ground, this research work sets out to unravel some of the origins of this controversy within the classical Arabic heritage, and provide some interpretations –despite being different in the modern era- in order to vindicate informative function of metrics since it is considered as one of its main constituents. All this is done within an interactional-relationship framework that orchestrates between the text creator, the text and the recipient